An Innovative Approach to Teaching the System of Linear Equations Module - Aziza Turapova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In solving the system of linear equations, it is important to improve the ability of students to think quickly, to facilitate the process of deep logical thinking, and to guide them through the algorithm of the problem.